The complete mitochondrial genome of Leizhou goat Capra hircus (Bovidae; Caprinae). (3rd March 2016) - Sun, Li-Qun; Guo, Gong-Liang; Wu, Jin-Yi; Zhang, Lei
Abstract: Leizhou goat ( Capra hircus ) is one of the famous native goat breed in China. In this study, the 16, 651 bp complete nucleotide sequence of Leizhou goat mitochondrial genome was sequenced for the first time. It contained 22 tRNA genes, 2 ribosomal RNA genes, 13 protein-coding genes.